2009
DOI: 10.1063/1.3065536
|View full text |Cite
|
Sign up to set email alerts
|

Controllable p-type doping of GaAs nanowires during vapor-liquid-solid growth

Abstract: The influence of the droplet composition on the vapor-liquid-solid growth of InAs nanowires on GaAs ( 1 ¯ 1 ¯ 1 ) B by metal-organic vapor phase epitaxyWe report on controlled p-type doping of GaAs nanowires grown by metal-organic vapor-phase epitaxy on ͑111͒B GaAs substrates using the vapor-liquid-solid growth mode. p-type doping of GaAs nanowires was realized by an additional diethyl zinc flow during the growth. Compared to nominally undoped structures, the current increases by more than six orders of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 21 publications
4
109
0
Order By: Relevance
“…So far, both p-and n-type doping have been achieved in Si, InP, GaN, or GaAs nanowires. [3][4][5][6] Tremendous progress has been made in the last years regarding the understanding of the incorporation mechanisms during the vapor-liquid-solid growth of nanowires. In particular, it has been shown that parasitic radial growth can lead to the formation of a highly doped shell in the nanowire.…”
Section: Introductionmentioning
confidence: 99%
“…So far, both p-and n-type doping have been achieved in Si, InP, GaN, or GaAs nanowires. [3][4][5][6] Tremendous progress has been made in the last years regarding the understanding of the incorporation mechanisms during the vapor-liquid-solid growth of nanowires. In particular, it has been shown that parasitic radial growth can lead to the formation of a highly doped shell in the nanowire.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, there have been studies focusing on the mechanisms and the limitations of dopant incorporation in nanowires. [6][7][8][9][10] Various challenges have been anticipated and/or found, such as the competition of dopant incorporation between the shell and the core of the nanowire and doping compensation. 6,7 Compensation can typically occur in amphoteric dopants such as silicon in GaAs.…”
mentioning
confidence: 99%
“…35,36 This can be mitigated by free charge carrier generation via sufficient doping. 36 Comparing the II/III ratio of 0.0016 used in this work to previously reported values, 37 the doping levels should exceed 10 18 cm À3 , which is expected to suffice for free charge carrier generation and thus enhance the PL properties. Similarly, the doping levels are assumed sufficiently high in NWs grown on AZO, especially near the NW base where the Zn incorporation is higher.…”
Section: Resultsmentioning
confidence: 99%